MANAGEMENT OF SOCIAL COMMUNITY OF INDONESIAN CHINESE CLAN IN BANTEN (International Conference on Social and Islamic Studies, 2021)
This research is motivated by a decrease in the number of followers of the social community. These followers decrease shows a decrease in the decision of the followers of the Chinese clan association that how the management of the Chinese clan community is in the midst of the increasingly stringent community phenomenon, which is based on the community management, the perception of the Chinese clan and the attitude of social needs for the Chinese clan in Banten. This research uses descriptive qualitative method. Data were collected using the Miles & Huburman model and observation techniques, interviewing six persons. The findings show that there is no improvement in the management of the Chinese clan social community, affecting theeducation sector which encourage the implementation of mandarin courses, scholarships, library procurement and book review.